Does Community Support in Moderating Roles Mitigate Short Comings in Rural Tourism Development? (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Rural tourism offers unique experiences and the potential to revitalize local economies. Objectives: This study explores the connection between tourism destination competitiveness, hard services (e.g., infrastructure),  soft services (e.g., hospitality), and the moderating role of community support within the Sundarbans National Park,  rural destination in West Bengal, India. Methodology: A quantitative approach was used to measure and analyse  numerical data, identifying relationships and drawing conclusions. This study employed this approach to examine how  community support influences rural tourism development. The primary data for this study was gathered through a  survey conducted among domestic tourists who had visited the Sundarbans. This survey offered direct insights into the  experiences and opinions of these tourists. SEM is used as it handles complex relationships between variables, i.e.,  community support and rural tourism development. Path analysis was conducted using PLS-4 to examine how various  forms of community support, such as hospitality, cooperations, etc. influence the development of tourism in Sundarbans.  Results: Results underscores the importance of hard and soft services combined key drivers of rural tourism destination  competitiveness setting. Moreover, strong community support significantly amplifies the positive effect of these services  on the competitiveness of the destination. Conclusion: The study offers valuable insights for rural tourism development,  emphasizing the significance of community connection in enhancing destination attractiveness and competitiveness.
Keywords: Sundarbans; hard and soft services; destination; SEM; domestic tourists